2018
DOI: 10.1155/2018/8367571
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Preterm Birth: Maternal Characteristics, Ultrasound Markers, and Biomarkers: An Updated Overview

Abstract: There is not a single or combined screening method for preterm birth with high sensitivity which will truly identify the women at risk for preterm birth while also with high specificity to prevent unnecessary interventions and high treatment costs. Measurement of cervical length is the most cost-effective method that is used in clinical practice. Bedside tests have also been developed for detecting markers like fetal fibronectin, insulin-like growth factor binding protein-1 (IGFBP-1), interleukin-6, and placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 75 publications
(74 reference statements)
0
54
0
11
Order By: Relevance
“…Biochemical point of care tests with measurement of fetal fibronectin (fFN), placental alpha‐microglobulin‐1 (PAMG‐1) or phosphorylated insulin‐like growth factor binding‐protein‐1 (phIGFBP‐1) in cervicovaginal fluid have been added in recent years to improve the prediction of PTB 4 . However, it is yet not clear what the optimal algorithm for the application of these new biochemical parameters will be – instead or in addition to the CL measurement 3 . Furthermore, a routine application of the commercial available kits will increase the financial burden with costs up to 50€ per test.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical point of care tests with measurement of fetal fibronectin (fFN), placental alpha‐microglobulin‐1 (PAMG‐1) or phosphorylated insulin‐like growth factor binding‐protein‐1 (phIGFBP‐1) in cervicovaginal fluid have been added in recent years to improve the prediction of PTB 4 . However, it is yet not clear what the optimal algorithm for the application of these new biochemical parameters will be – instead or in addition to the CL measurement 3 . Furthermore, a routine application of the commercial available kits will increase the financial burden with costs up to 50€ per test.…”
Section: Introductionmentioning
confidence: 99%
“…Two meta-analyses of 116 different biomarkers from 217 studies over a period of four decades [ 115 ] and 30 novel biomarkers investigated over ten years [ 116 ] concluded that none of the investigated biomarkers can be considered clinically useful to predict PTB. In recent years, biomarkers that have been actively investigated for PTB include epigenetics (DNA methylation, histone modifications and microRNAs) [ 117 ], novel ultrasound markers (uterine artery pulsatility index, placental strain ratio and anterior cervical angle), and cervicovaginal, amniotic fluid and serum markers such as adipokines [ 118 ]. Adipokines play an important role in maternal-foetal adaptions and as such their expression has been demonstrated to vary during pregnancy and pregnancy complications [ 53 , 54 , 55 ].…”
Section: Adiponectin In Common Pregnancy Disordersmentioning
confidence: 99%
“…However, screening for PTB remains difficult in the absence of specific tests that would identify potential mothers at high risk of preterm birth. Although, the cervical length and cervico-vaginal fetal fibronectin measurements have been used with some success [5]. In addition, recent meta-analyses show there is no effective risk scoring system for prediction of PTB [6].…”
Section: Introductionmentioning
confidence: 99%